IDENTIFIKASI UANG KERTAS BERDASARKAN WARNA DENGAN METODE TEMPLATE MATCHING (Information Technology and Telematics, 2013)
With its technological amends, media forwarding even information progressively medley. One of it is one get bearing with object recognition. object recognition's application already there is one of it is process to identify image on bank note bases RGB. In this final project will design build to identify bank note eye bases RGB.   Colour characteristic an image gets to be declared for deep shaped histogram of that image one set down by h (r,g,b ), where h (r,g,b ) are total its appearances color couple r (red), g (green) and b (blue) one particular.   This project intent to identify rupiah money bases color resemblance. Identification is done about item bank note. Identified bank note type is prevailing rupiah bank note at Indonesia, which is fraction a thousand, two thousand, five thousand, ten thousand, twenty thousand, fifty thousand and a hundred thousand rupiahs.  To determine color characteristic of a bank note object utilized by count average histogram ruddles, green and blue. To know resemblance did by accounts distance of histogram point on their pictured pattern and query. If both of image has minimal distance, therefore gets to be concluded that image second that has resemblance.  Application program was built to utilize Delphi program application 7. Program are built to keep pattern data draw and matching draws query with aughts pictured data on patterns. Keyword : Image, rgb, money, matching